The impact of COVID-19 on students’ anxiety and its clarification: a systematic review - Wu, Jiarun; Kuan, Garry; Lou, Hu; Hu, Xiaoyu; Masri, Mohamad Najmi; Sabo, Abdulwali; Kueh, Yee Cheng (Frontiers in Psychology, 2023)
Introduction Since the emergence of COVID-19 in 2019, every country in the world has been affected to varying degrees. Long-term psychological pressure and anxiety will inevitably damage the physical and mental health of students. This study aimed to examine the effects of the COVID-19 pandemic on students who experienced stress and anxiety and to clarify which intervention was more effective. Methods A comprehensive literature search was conducted between January 2020 and December 2022 using online databases such as PubMed, Web of Science, Scopus, and Google Scholar by using the following keywords in combination: “COVID-19,” “stress,” “anxiety,” “depression,” and “intervention.” The retrieved literature was screened and reviewed. Results A total of 2,924 articles were retrieved using subject and keyword searches. After screening through the titles and abstracts, 18 related studies were retained. Their review revealed that: (1) most studies did not use medication to control stress and anxiety; (2) the standard methods used to reduce stress and anxiety were religion, psychological counseling, learning more about COVID-19 through the media, online mindfulness courses, improving sleep quality, and physical exercise; (3) the most effective interventions were physical activity and raising awareness about COVID-19 through the media and online mindfulness programs. However, some studies show that physical activity cannot directly relieve psychological stress and anxiety. Conclusion Limited interventions are effective, but learning more about COVID-19 and using active coping strategies may help reduce stress and anxiety. The implications of COVID-19 are also discussed.